Analysis of Student Satisfaction Questionnaire with 2D Autocad Learning Media in Learning Road and Bridge Construction - Pujiastuti, Elfisana; Rufi’i, Rufi’i (research, training and philanthropy institution Natural Aceh, 2024)
The aim is to determine students' satisfaction level in class XI using Autocad 2D learning media in road and bridge construction lessons. This study also shows that 2D AutoCAD-based learning can help students understand the material better and become more adept at drawing. Non-test evaluation data from student satisfaction questionnaires in class XI DPIB were analyzed. Students were asked to determine their perceptions, preferences, and level of satisfaction with the application. To make educational media based on the Autocad 2D application to concentrate on road and bridge construction lessons more efficient and practical. The Likert Scale Model is used for research and development. The Likert scale is a scale that can be used to measure the attitudes, opinions and perceptions of students or groups of students about the benefits and how effective the use of this media is. From the results, the conclusion that can be drawn is that the AutoCAD 2D application in learning Road and Bridge Construction drawings is considered positive and very good in helping students' learning, as evidenced by the results of the percentage of student responses with the results obtained being 85% to 90%, which means students feel delighted. Moreover, it makes learning two 2-dimensional Autocad-based drawings easier in Road and Bridge Construction lessons.